Contribution of modern industrial revolutions to securing socio-economic systems during the war against Ukraine - Leonid Melnyk; Laszlo Vasa; Oleksandr Kubatko; Inna Koblianska; Pavlo Hrytsenko (Problems and Perspectives in Management, 2025)
The modern industrial revolutions have significantly influenced social and political landscapes, prompting critical inquiries into the security and integrity of socio-economic systems, particularly in the context of military confrontation. This paper investigates the role of disruptive technologies associated with Industries 3.0, 4.0, and 5.0 in safeguarding socio-economic systems amid the ongoing russian war against Ukraine. The paper highlights how modern technologies have bolstered system resilience and adaptability by examining progress in green energy, transport transition, and the development of digital infrastructure and services before the war. Green energy and transport technologies have been instrumental in decentralization, energy networking, compensating for energy losses, and mitigating disruptions caused by the war. The proliferation of electric vehicles and the expansion of charging infrastructure have significantly reduced the potential impact of aggression, facilitating evacuations and supporting essential services during fuel shortages. Digital technologies have played a crucial role in ensuring continued access to education, employment, and communication, thereby strengthening societal resilience and reinforcing human capital, a key factor in socio-economic system security. This marks a shift from a technocratic to a system-synergistic, human-centered security model, where human capital becomes a core determinant of resilience, and technologies evolve from mere tools into integral elements of a sustainable socio-economic structure. Nevertheless, challenges related to technological dependencies, such as supply chain vulnerabilities and cyber threats, require further investigation in future research. AcknowledgmentsThe paper is prepared within the scientific research projects “Digital Transformations to Ensure Civil Protection and post-war Economic Recovery in the Face of Environmental and Social Challenges” (No. 0124U000549) and “Fundamental Grounds for Ukraine’s transition to a digital economy based on the implementation of Industries 3.0; 4.0; 5.0” (No. 0124U000576).